IMPACT OF DISCLAIMER DUE TO COVID-19 ON THE RELIGIOUS VALUE OF OFFICIAL WORKERS - Fikriyah, Siti Zakiyatul; Mumtahanah, Khoirul; Amaliyah, Khasiatun (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2021)
The Covid-19 virus is one type of infectious disease or infectious disease that emerged in Wuhan, China in December 2019. And began to spread in Indonesia in March 2021. The increasing number of positive cases and deaths due to Covid-19 has led the government to implement several policies, namely restrictions on Large-Scale Social Affairs (PSBB) and working from home. This policy has a very big impact on employers because they experience enormous losses so that company leaders carry out layoffs (layoffs) on a large scale or on a large scale. The impact of the termination of employment is felt directly by the workers concerned. And social changes began to occur in workers who were laid off (changes in religiosity), such as what happened in Dongos Village, Kedung District, Jepara Regency. This study aims to see the impact and influence factors of layoffs due to Covid-19 on the religious level of workers who were laid off and who were not laid off. The method used is a combined research approach (quantitative and qualitative), using a questionnaire and direct interviews. The results obtained indicate that layoffs due to Covid-19 affect the level of religiosity of laid-off workers. Moreover, there is a difference in the level of religiosity between workers who were laid off and those who were not. The factors that influence the impact of layoffs due to Covid-19 on the level of worker religiosity are 1) Ideological, 2) Ritualistic, 3) Expressive, and 4) Consequences